Multidisciplinary management of tracheobronchial injury. (26th January 2022) - Boutros, Jacques; Marquette, Charles-Hugo; Ichai, Carole; Leroy, Sylvie; Benzaquen, Jonathan
Tracheobronchial injury is a heterogeneous entity comprising multiple rare and potentially life-threatening scenarios. We performed a systematic literature review focusing on post-intubation tracheal injuries (PiTIs) and post-traumatic tracheobronchial injuries (PTTBIs). PiTIs are often longitudinal lacerations of the middle third of the membranous trachea. Subcutaneous emphysema of the face and trunk following tracheal intubation should immediately trigger the diagnosis. Diagnosis may be suspected on the chest computed tomography (CT) and should be confirmed by bronchoscopic examination. Conservative management is encouraged for a spontaneously breathing or stable patient on noninvasive ventilation. Surgical repair is mandatory when mechanical ventilation is required and if bridging of the injury is impossible. PTTBIs are often associated with other severe injuries. Patients often present with massive subcutaneous emphysema and intractable pneumothorax. Diagnosis may be suspected on the chest CT and should be confirmed by bronchoscopic examination. Early surgical repair is indicated. In selected patients, conservative management can be considered. Tracheobronchial injuries are heterogeneous, comprising rare and potentially life- threatening scenarios. Post-intubation tracheal/post-traumatic tracheobronchial injuries need multidisciplinary evaluation and some cases may be managed conservatively. https://bit.ly/3kug4ud